The Influence of Mudharabah, Murabahah, and Ijarah Financing on Return on Assets in Islamic Commercial Banks in Indonesia - Swarli, Yousf Bellin (Lembaga Riset Mutiara Akbar, 2025)
The purpose of this study is to analyze the influence of Mudharabah, Murabahah and Ijarah variables on the Return on Assets (ROA) of Indonesian Islamic General Banking based on business units carried out in the period January 2019 to December 2023. The data analysis method used is multiple linear regression including the classical assumption test. Based on the results of the partial test (T-Test) the Mudharabah variable does not have a significant effect on Return on Assets (ROA) because the significance value is 0.402 more than 0.05 with a positive direction of influence or coefficient value. The Murabahah variable has a significant effect on Return on Assets (ROA) because the significance value is 0.00 less than 0.05 with a positive direction of influence or coefficient value. The Ijarah variable has a significant effect on Return on Assets (ROA) because the significance value is 0.02 less than 0.05 with a positive direction of influence or coefficient value. The results of the simultaneous test (F Test) of all independent variables (Mudharabah, Murabahah, Ijarah) significantly influence the dependent variable (Return on Asset) with a significance value of 0.00 less than 0.05. The influence of independent variables simultaneously on the dependent variable is 27.9% and 72.1% is influenced by other variables outside the study or outside the regression model.